2014
DOI: 10.3389/fpsyg.2013.00987
|View full text |Cite
|
Sign up to set email alerts
|

Volitional components of consciousness vary across wakefulness, dreaming and lucid dreaming

Abstract: Consciousness is a multifaceted concept; its different aspects vary across species, vigilance states, or health conditions. While basal aspects of consciousness like perceptions and emotions are present in many states and species, higher-order aspects like reflective or volitional capabilities seem to be most pronounced in awake humans. Here we assess the experience of volition across different states of consciousness: 10 frequent lucid dreamers rated different aspects of volition according to the Volitional C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 54 publications
(67 reference statements)
2
35
0
2
Order By: Relevance
“…Furthermore, the watching self can influence dream continuation and command changes in dream content [ 66 ]. Previous electrophysiological (EEG) and functional magnetic resonance imaging (fMRI) studies showed that lucid dreaming is related to increased phase synchrony and increased gamma frequency activity at around 40 Hz in fronto-temporal brain regions [ 67 - 69 ]. A recent transcranial magnetic brain stimulation (TMS) study by Voss et al .…”
Section: Dreamsmentioning
confidence: 99%
“…Furthermore, the watching self can influence dream continuation and command changes in dream content [ 66 ]. Previous electrophysiological (EEG) and functional magnetic resonance imaging (fMRI) studies showed that lucid dreaming is related to increased phase synchrony and increased gamma frequency activity at around 40 Hz in fronto-temporal brain regions [ 67 - 69 ]. A recent transcranial magnetic brain stimulation (TMS) study by Voss et al .…”
Section: Dreamsmentioning
confidence: 99%
“…However, lucidity has the advantage that one can actively decide to practice and what and how to practice. Dresler et al (2014) showed that experienced volition in lucid dreams is comparable to wakefulness and higher than in non-lucid dreams. In particular, intention enactment and self-determination were pronounced in lucid dreams compared to non-lucid dreams.…”
Section: Preconditions and Recommendationsmentioning
confidence: 97%
“…Anders herum ist beim Klarträumen mehr DLPFC-Aktivität zu beobachten als im regulären REM- Schlaf. Patienten mit einer Psychose fehlt also die Einsicht über den eigenen Zustand und damit genau die Einsicht, die einen luziden Traum von einem nicht-luziden Traum unterscheidet (31). Training mit luziden Träumen könnte sich daher in Zukunft als hilfreich bei der Behandlung von Psychosen erweisen.…”
Section: Psychotherapieunclassified